Didelphys uterus in pregnant patient - Viacava Menéndez, Manuel (2023)
Congenital anomalies of the uterus are a rare pathology, in which the didelphys uterus represents 11% of these malformations. Early diagnosis is important to carry out adequate prenatal control. Only 20% to 30% of cases of uterus didelphys reach term. Imaging techniques (ultrasound, hysterosalpingography, and magnetic resonance) allow us an accurate diagnosis that leads to a prognosis for reproductive function. This case shows us an early clinical, gynecological, and ultrasound diagnosis, early diagnosis of pregnancy in the right uterus, adequate prenatal control, and the right case solution for mother and child.